NEGOTIATING ACEH SELF-DETERMINATION IN INDONESIA’S UNITARY SYSTEM: A Study on Peace Agreement Helsinki Memorandum of Understanding 2005 - M. Y. Aiyub Kadir (Aceh International Journal of Social Science, 2012)
Abstract - Aceh, the northern-most province of Indonesia came through long suffering of armed conflicts for self-determination under the Dutch (1873-1942) and Japanese colonisation (1942-1945). It continued until Aceh joined Indonesia‟s unitary system in 1945, in which it was formally initiated by Tgk. Daud Beureueh between 1953-1963, and further to be declared by Tgk. Hasan Tiro on 4th December 1976 under the banner of the Free Aceh Movement (GAM). This struggle was ended by peace agreement, the Helsinki Memorandum of Understanding (MoU) on 15th August 2005 with the Aceh self-government notion consensus. In this regard, Aceh has more spaces and opportunities to re-determine its political, economic, social and cultural status under the Indonesian system. According to the international law, the notion of self-government is considered as internal self-determination under the International Human Rights Law regime. This would refer to two covenants: the United Nations International Covenant on Civil and Political Rights and on Economic, Social and Cultural Rights 1966. However, in practice, despite this ongoing implementation has achieved some progress in short term local political development, yet there are still many challenges for long-term economic, social and cultural advancement objectives, in particular regarding human rights related issues. This paper endeavours to analyse the issue through the overview of historical background of Aceh self-determination from an international law perspective. Hopefully, this paper contributes to a conceptual understanding of the MoU Helsinki in terms of Aceh self-determination movement as well as some challenges ahead.